Single incision laparoscopic appendicectomy versus conventional laparoscopic appendicectomy- a prospective study - Kumar, Rohit; Vaithianathan, Rajan; Sundaresan, Vinoth (International Surgery Journal, 2017)
Background: The advent of Single incision laparoscopic appendicectomy (SILA) has encouraged surgeons to compare its benefits over conventional laparoscopic appendicectomy (CLA). We conducted a prospective study comparing SILA with CLA, evaluating parameters like operative time and complications, post-operative pain, duration of stay and the cosmetic outcome. Methods: A prospective, comparative study of 94 consecutive patients was conducted at our institution between December 2014 and May 2016. The data regarding the various parameters were documented in both groups of patients. Results: Among the 94 patients, 30 underwent SILA and 64 underwent CLA. We found statistically significant outcomes for SILA over CLA in variables such as operative time (p=0.0018), duration of hospital stay (p≤0.0001) and cosmetic outcome (p≤0.0001). Almost all patients in the SILA category showed no evidence of a scar after a three month follow up. Conclusions: SILA was found to have a better outcome than CLA with regard to operative time, hospital stay and cosmesis. We conclude that this technique of SILA can be a better alternative to CLA.